CNS Histiocytosis- Rare Disease with An Unusual Manifestation - Sadekar, Saurabh; Swathi, Alluri; Mridula, Kandadai Rukmini; Chakradhar, N.; Arpita, C.; Balasubramanian, Anand; Bandaru, VCS Srinivasarao; Chaudhuri, Jaydip Ray (Journal of Advances in Internal Medicine, 2023)
CNS histiocytosis is a rare and debilitating disease with multiple presentations. We here present a rare case of histiocytosis in a 4 year old child manifesting with diplopia as the sole neurological symptom. The patient had only saccadic abnormalities on examination and lesions in tectal pons and cerebellum. Initially considering the possibility of demyelinating disorder, steroids were given with partial resolution of signs but no improvement in signs or MRI imaging. Biopsy gave the diagnosis. The diagnosis of CNS histiocytosis should be considered even in patients with few symptoms and actively evaluated for.